2020
DOI: 10.1590/s0102-053620200409
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters and simultaneous selection using traits of ornamental interest in pepper plants

Abstract: Pepper plants of the genus Capsicum are widely grown worldwide. The Capsicum annuum species shows ornamental potential; nevertheless, in the state of Piauí, there has been a lack of studies on its performance, related to quality traits needed to meet market demand. The aim of this study was to estimate the genetic parameters and associations between traits of ornamental interest in C. annuum in order to indicate, by simultaneous selection of traits, accessions to start an ornamental pepper breeding program in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…Estes coeficientes, possuem um papel importante nos programas de melhoramento, oferecendo uma análise da influência relativa dos fatores genéticos e ambientais na variação das características fenotípicas (KAROLINA et al, 2020). Os resultados obtidos podem direcionar a seleção dos melhores indivíduos, de forma acurada, otimizando a eficácia dos programas de melhoramento Tabela 1.…”
Section: Resultsunclassified
“…Estes coeficientes, possuem um papel importante nos programas de melhoramento, oferecendo uma análise da influência relativa dos fatores genéticos e ambientais na variação das características fenotípicas (KAROLINA et al, 2020). Os resultados obtidos podem direcionar a seleção dos melhores indivíduos, de forma acurada, otimizando a eficácia dos programas de melhoramento Tabela 1.…”
Section: Resultsunclassified
“…Low coefficient of determination (9.5%) and high residual effect (95%) were found in the trail analysis. Acevedo et al (2020) estimated direct and indirect effects of six agronomic characteristics, including number of days for maturation, fruit length and width, and number of fruits per pepper plant (C. annuum) and found high residual effect (79%). Salla et al (2015) found low coefficient of determination (12%) and high residual effect (93%) for the evaluated characteristics of Plinia cauliflora plants, with similar values to those found in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Despite of these low values, the explanatory variables did not need to be totally discarded due to low direct effect on the base variable; thus, an alternative is the use of selection indexes that can provide information on favorable gains in many characteristics (Cruz et al, 2014;Acevedo et al, 2020). Mulamba and Mock (1978) is among these selection indexes; it ranks the genotypes for each characteristic by attributing higher absolutes values to those of better performance and, then, the values attributed to each characteristic are summed, obtaining the sum of the ranks, which determines the genotype classification (Cruz & Regazzi, 2001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…high temperature) (T. dos S. Ferreira The size of the pepper plant in the pot is one of the main quality attributes observed by the ornamental plant sector and not every pepper plant can be considered ornamental. The desired ideotype includes, among other factors, the harmony between the plant and the pot given by the balance between plant height and canopy diameter in relation to the size of the pot used (Acevedo et al, 2020;do Rêgo & do Rêgo, 2018). Very tall plants with a wider crown do not adapt well to the pot, resulting mainly in the plants tipping over.…”
Section: Introductionmentioning
confidence: 99%